The Importance of Intervention During the Critical Period to Support Individual Development - Nabila Atika Ajra; Yuliana Intan Lestari (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study discusses critical periods in human development and intervention strategies that can support optimal individual growth at every stage of life. Critical periods are phases when individuals are highly sensitive to environmental stimulation, so the experiences received greatly influence physical, cognitive, social, and emotional development. This study aims to explain the concept of critical periods, the forms of critical periods in human development, the impacts of failure in handling critical periods, and intervention strategies that can be implemented by families, schools, and professionals. The research method used is library research with a qualitative descriptive approach through the analysis of scientific literature, developmental psychology books, and related journals. The results show that critical periods occur from the prenatal stage, infancy, early childhood, to adolescence. Lack of stimulation and environmental support during these stages can cause delays in language, social, emotional, and cognitive development. Intervention strategies such as responsive parenting, developmental stimulation, early detection, developmentally appropriate education, and professional support are important in helping individuals successfully pass through critical periods. Therefore, collaboration among families, schools, communities, and professionals is essential to support optimal human development.